Blood Pressure and Heat Shock Protein 70 Levels Related to Acute Ischemic Stroke Severity - Indra, Syarif; Khair, Umul; Trisna, Yulia (Green Medical Journal, 2020)
Introduction: Hypertension is a risk factor of ischemic stroke, the prevalence of ischemic stroke in Indonesia is 34.1%. Heat Shock Protein (HSP) 70 increases in hypertension and acute phase of ischemic stroke. To determine differences of blood pressure (BP) and HSP 70 levels, related to the acute ischemic stroke severity. Methods: This was a cross-sectional study that was carried out in the Neurological Ward of Dr.M.Djamil Hospital and National Stroke Hospital, from May to September 2019. Inclusion criteria were obtained consecutively. BP was measured with a sphygmomanometer, stroke severity was measured by NIHSS, and HSP 70 levels was analyzed by the ELISA. Computerized statistical analyzes were performed using SPSS software version 23.0 for windows. The result was statistically significant if the p-value < 0.05. Results: There were 40 samples consisted of 26 (65%) male, mean age 59.78 years. The systolic BP ranging from 130 to 190 mmHg (median 160), the diastolic BP ranging from 70 to 100 mmHg (median 90), the HSP 70 levels ranging from 2.50 to 19.56 ng/mL (median 2.72). There were 18 patients with mild stroke and 22 patients with moderate stroke. There was no significant difference between systolic blood pressure (SBP), diastolic blood pressure (DBP), and severity of stroke (p=0,369; p=0,221, respectively). There was no significant difference between HSP 70 levels and the severity of stroke (p=0,312). There was no relation between the degree of BP and HSP 70 levels. Conclusion: There were no significant differences of SBP, DBP, and HSP 70 with the acute ischemic stroke severity.